Cytotoxic conjugates of betulinic acid and substituted triazoles prepared by Huisgen Cycloaddition from 30-azidoderivatives - Sidova, Veronika; Zoufaly, Pavel; Pokorny, Jan; Dzubak, Petr; Hajduch, Marian; Popa, Igor; Urban, Milan (PloS one, 2017)
In this work, we describe synthesis of conjugates of betulinic acid with substituted triazoles prepared via Huisgen 1,3-cycloaddition. All compounds contain free 28-COOH group. Allylic bromination of protected betulinic acid by NBS gave corresponding 30-bromoderivatives, their substitution with sodium azides produced 30-azidoderivatives and these azides were subjected to CuI catalysed Huisgen 1,3-cycloaddition to give the final conjugates. Reactions had moderate to high yields. All new compounds were tested for their in vitro cytotoxic activities on eight cancer and two non-cancer cell lines. The most active compounds were conjugates of 3β-O-acetylbetulinic acid and among them, conjugate with triazole substituted by benzaldehyde 9b was the best with IC50 of 3.3 μM and therapeutic index of 9.1. Five compounds in this study had IC50 below 10 μM and inhibited DNA and RNA synthesis and caused block in G0/G1 cell cycle phase which is highly similar to actinomycin D. It is unusual that here prepared 3β-O-acetates were more active than compounds with the free 3-OH group and this suggests that this set may have common mechanism of action that is different from the mechanism of action of previously known 3β-O-acetoxybetulinic acid derivatives. Benzaldehyde type conjugate 9b is the best candidate for further drug development.
Keywords: Benzaldehydes; lidé; kyselina betulinová; cykloadiční reakce; Cell Line, Tumor; Antineoplastic Agents; Cell Survival; buněčný cyklus; protinádorové látky; triazoly; Cell Cycle; triterpeny; Humans; Triterpenes; Cycloaddition Reaction; pentacyklické triterpeny; Betulinic Acid; viabilita buněk; Pentacyclic Triterpenes; Triazoles; benzaldehydy; nádorové buněčné linie